2021
DOI: 10.7759/cureus.19211
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Homocysteine With Gender, Blood Pressure, Body Mass Index, Hemoglobin A1c, and the Duration of Diabetes Mellitus Type 2

Abstract: Introduction Increased levels of homocysteine (Hcy) may lead to endothelial damage and increase the risk of cardiovascular and renal malfunction. The current study aimed to evaluate the association of serum Hcy levels with gender, body mass index (BMI), duration of diabetes mellitus type 2 (DMT2), hemoglobin A1c (HbA1c), and blood pressure (BP). Methodology A prospective observational study was conducted at Hayatabad Medical Complex in Peshawar, Pakistan in the department of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“… 61 Noor et al also found that patients with diabetes mellitus and hypertension are likely to have increased levels of Hcy and, therefore, must be regularly screened for hyperhomocysteinemia. 62 The higher levels of serum homocysteine and lower levels of serum betaine are associated with an increased risk of microangiopathy in patients with diabetes. 63 For type 1 diabetes, fasting plasma total homocysteine concentrations were within normal limits in children and adolescents who were without any clinical evidence of microvascular and macrovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“… 61 Noor et al also found that patients with diabetes mellitus and hypertension are likely to have increased levels of Hcy and, therefore, must be regularly screened for hyperhomocysteinemia. 62 The higher levels of serum homocysteine and lower levels of serum betaine are associated with an increased risk of microangiopathy in patients with diabetes. 63 For type 1 diabetes, fasting plasma total homocysteine concentrations were within normal limits in children and adolescents who were without any clinical evidence of microvascular and macrovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…En el enfoque clínico se detecta la obesidad mediante el Índice de Masa Corporal (IMC), que se calcula dividiendo el peso en kilogramos entre la estatura en metros cuadrados. Un IMC alto (≥25 Kg/m 2 ) podría estar relacionado de forma directa o indirecta con la progresión de la Enfermedad Renal Crónica (ERC), sin embargo, hasta el momento la literatura médica aún no tiene las bases suficientes para constatar esta relación [4][5][6] . Los individuos obesos desarrollan una hiperfiltración glomerular (glomerulopatía) en respuesta a una compensación metabólica secundaria, producto de su aumento de peso 2 .…”
Section: Introductionunclassified